Genistein Suppresses Spontaneous Oviduct Tumorigenesis in Quail - Şahin, Kazım; Akdemir, Fatih; Tuzcu, Mehmet; Şahin, Nurhan; Onderci, Muhittin; Ozercan, Resat; Küçük, Ömer (Routledge Journals, Taylor & Francis Ltd, 2009)
Spontaneous leiomyomas of the oviduct are common tumors of the Japanese quail (Coturnix coturnix japonica) and laying hens. This makes it a good animal model for screening potential agents for testing in the prevention and treatment of human myoma uteri. Genistein has been shown to inhibit the growth of various cancer cells. We investigated the effects of genistein supplementation on the development of fibroid tumors in the oviduct, serum oxidative stress markers [malondialdehyde (MDA), 8-isoprostane, 4-hydroxyalkenal (HAE), 8-hydroxy-2'-deoxyguanosine (8-OHdG) levels], soy isoflavone levels, and tissue biomarkers [Connexin 43 (Cx43), Bcl-2, and Bax and heat shock protein 70 (Hsp70)expression] in Japanese quail. One hundred and fifty quail (12 mo old) were assigned to 3 experimental groups as 5 replicates of pens containing 10 birds in each. Birds were fed either a basal diet or the basal diet supplemented with 400 mg or 800 mg of genistein/kg of diet. The animals were sacrificed after 315 days, and the tumors were identified. Genistein supplementation significantly decreased the incidence of fibroid tumors as compared to control birds (P = 0.04). The tumors in genistein-fed birds were smaller than those found in control birds (P = 0.02). Serum MDA, 8-isoprostane, and HAE levels were lower in treatment groups than in control group (MDA: 2.01 vs. 0.82; 8-isoprostane: 135 vs. 101; HAE: 1.45 vs. 0.73; P <= 0.01). The concentrations of serum 8-OHdG, which is a marker of oxidative damage, in the groups were 27.5, 22.4, and 21.3 ng/ml, respectively (P = 0.05). The expression of cell cycle regulatory proteins, Bcl-2, was 4.18 and 4.61 in the genistein groups and 6.21 in the control group, and the expression of Bax was 10.93 and 16.78 in the genistein groups and 7.60 in the control group (P < 0.001 for Bax). Cx43 level was 2.56 and 2.40 in the genistein groups compared with 5.15 in the control group. None of the differences in the Cx43 and Bcl-2 of the groups were significant. The expression of heat shock proteins, Hsp60 and Hsp70, were not different between groups, although Hsp70 level of the genistein groups (19.73) was lower than the control group (27.8). The results indicate that dietary supplementation of genistein reduces the incidence and size of spontaneously occurring leiomyoma of the oviduct in the Japanese quail. Clinical trials should be conducted to investigate the efficacy of genistein supplementation in the prevention and treatment of uterine leiomyoma in humans.
1st International Congress on Nutrition and Cancer -- MAY 19-23, 2008 -- Antalya, TURKEY
Keywords: Oxidative Dna-Damage; Soy Isoflavone Supplementation; Leiomyoma Cell-Proliferation; Human Uterine Leiomyomas; Estrogen-Receptor; in-Vitro; Menstrual-Cycle; Cancer Cells; Kappa-B; Inhibition